EVALUATION OF THE EFFECTIVENESS OF MODERN TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF THE COLLEGE - D. Smolyakova (Вестник университета)
This article deals with the evaluation of the effectiveness of modern technologies in the educational process of the college contributing to the innovative formation of the educational process in the college (for example Sevastopol College of service and trade). The assessment of satisfaction of consumers of educational services is one of the elements of ensuring quality of educational process. The results of internal monitoring of the educational environment are the basis for various kinds of proactive or corrective actions for the institutions of the act, engaged in the training of highly qualified specialists. One of the possible options for obtaining information about the activities of the educational institution in this direction is the survey of recipients of educational services (students).